Saudi Arabia : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Saudi Arabia's launch of a bold reform program under Vision 2030, announced in 2016. The authorities have made considerable progress in initiating the implementation of their ambitious reform agenda. Non-oil growth is projected to pick up to 1.7 percent in 2017. Growth is expected to strengthen over the medium term as structural reforms are implemented. Risks mainly come from uncertainties about future oil prices, as well as questions about how the ongoing reforms will affect the economy. Employment growth has weakened, and the unemployment rate among Saudi nationals has increased to 12.3 percent. The fiscal deficit is also projected to narrow substantially in the coming years.